Glucose Sensing Optionally in Optical and Optoelectrical Modes Based on Au-TiO2 Schottky Nanojunctions (Journal of Solar Energy Research Updates, 2024)
Abstract: In recent years, metallic nanostructures have been extensively researched in the field of plasmonic for optical and optoelectronic applications such as biochemical sensing. However, an additional optoelectronic converter or spectrometer is usually required for the sensing application. Herein, the orderly-patterned Au-TiO2 Schottky junction with an Al film that we coupled, which simultaneously works as an optical reflector and conducting layer, can achieve optical sensing of glucose by exciting surface plasmon resonance associated with the environment, and meanwhile can realize glucose detection with direct electrical-signal readout by collecting the photogenerated carriers inside the Au nanostructures and TiO2 film. When used in optical mode, the designed sensor shows a sensing sensitivity of up to 1200.0 nmRIU-1 in numerical calculation, and the measured value is 346.1 nmRIU-1. When used in optoelectrical mode, the glucose sensor under one-sun illumination obtains a sensitivity of 70.0 µAM-1cm-2 in the concentration range of 0–10 mM, with a detection limit of 0.05 µM (Signal/Noise=3). Simulation and experimental results demonstrated that the Al-film-coupled Au-TiO2 Schottky nanojunction can monitor glucose concentration optionally in optical and optoelectrical modes, which presents an alternative route to the miniaturized, portable, and multi-functioned sensors.